KEMAMPUAN MEMAHAMI ISI BERITA KORAN KOMPAS SISWA KELAS XII SMAN 1 MINAS - Bintang Rumiris Pasaribu; Auzar '; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve the ability to understand the content of newspaper stories compass class XII student of SMAN 1 Minas. This research subject is class XII SMAN 1 Minas totaling 65 students. To obtain the necessary data in this research is to take four different text news theme or issue. News that shaped news news pertained opinions / facts. Any news on the tests using the formula 5W + 1H through a multiple-choice objective test with 5 options. The results of this study indicate that the ability to understand the content of newspaper articles were categorized compass with an average value of 70.9. The ability to understand the elements of why it is the lowest category with a percentage of 57.30 Due in understanding why the elements means that students should be able to tell why these events happen and categorized as low.Keywords: understanding, news content, 5w + 1h